Pengaruh program Praktik Kerja Lapangan (PKL) SMKS Yasipa Terpadu jurusan Tata Busana terhadap peningkatan kompetensi siswa - Gani, Abdul; Rasyid, Kemal Muhammad; Al-Khatib, Ibadurrahman; Mubin, Shofwan Nurul; Aziz, Maulana; Baharudin, Agus; Hartono, Rudi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
Vocational High School education is expected to produce graduates who are in accordance with the needs of the industrial world. SMKS Yasipa Terpadu Pelabuhan Ratu majoring in Fashion Design seeks to achieve this goal with a Field Work Practice program in collaboration with PT. Lydia Sola Gracia. This study seeks to see the effectiveness of Field Work Practices in improving student competence from an industry perspective. The competencies of the students studied are hard skills, namely sewing productivity and soft skills, namely the level of student discipline between before and after field work practice. The study took a sample of grade XI students of Vocational High School. The research was carried out at SMK Yasipa Terpadu Pelabuhan Ratu academic year 2022/2023. The data in this study was taken from the population and sample of the study, namely class XI students of the Fashion Department. The example in this study was chosen using a census technique where the entire population was sampled, namely as many as 46 students. The results showed an increase in the average score of student sewing competence after participating in PKL, from 50.33 to 74.78. The results of the Wilcoxon difference test stated that there was a real influence of the PKL program on improving student competence. While this cooperation program does not affect the improvement of student discipline. Abstrak Pendidikan Sekolah Menengah Kejuruan diharapkan menghasilkan lulusan yang sesuai dengan kebutuhan dunia industri. SMKS Yasipa Terpadu Pelabuhan Ratu jurusan Tata Busana berupaya mencapai tujuan tersebut dengan program Praktik Kerja Lapang bekerja sama dengan PT. Lydia Sola Gracia. Penelitian ini berusaha melihat efektivitas Praktik Kerja Lapang dalam peningkatan kompetensi siswa dari perspektif industri. Kompetensi siswa yang diteliti adalah hard skill yaitu produktivitas menjahit dan soft skill yaitu tingkat kedisiplinan siswa antara sebelum dengan sesudah praktik kerja lapang. Penelitian mengambil sampel siswa kelas XI Sekolah Menengah Kejuruan. Penelitian dilaksanakan di SMK YASIPA Terpadu Pelabuhan Ratu pada Tahun Pelajaran 2022/ 2023. Data dalam penelitian ini diambil dari populasi dan contoh penelitian yaitu siswa kelas XI Jurusan Tata Busana. Contoh dalam penelitian ini dipilih dengan menggunakan teknik sensus di mana seluruh populasi menjadi contoh yaitu sebanyak 46 orang siswa Hasil penelitian menunjukkan terdapat peningkatan skor rata-rata kompetensi menjahit siswa setelah mengikuti PKL yaitu dari 50,33 menjadi 74,78. Hasil uji beda Wilcoxon menyatakan bahwa terdapat pengaruh yang nyata program PKL terhadap peningkatan kompetensi siswa. Sedangkan program kerja sama ini tidak berpengaruh terhadap peningkatan kedisiplinan siswa.